Factors influencing the use of coconut oil by the householders in Sri Lanka and their policy relevance to popularize the consumption of coconut oil - T. S. G. Peiris; M. T. N. Fernando; S. Samarajeewa (International Coconut Community Journal, 2004)
In recent past the concept on the use of coconut oil (CNO) by the householders in Sri Lanka has been changing due to various reasons. The reasons were studied using the generalized linear models for the survey conducted during May/June 2001 for 366 householders representing three different population sectors (urban, rural and estate) and different income groups. The significant factors influencing the use of CNO are the type of oil used in past, monthly income, quality of CNO, misconception about CNO and the population sectors. The percentage of non-CNO users is considerably higher in the urban sector, whereas CNO still is the major edible oil in the rural and estate population sectors of Sri Lanka. The percentage of householders using CNO in the sample was 91.2. In 75% of the sample, the quantity of CNO consumption per person has reduced over the last five years. The main reason for dissatisfaction for CNO is adulteration. The proportion of CNO use was significantly higher in lower income groups than the higher income groups. The proportion of the CNO use decreased sharply when the income increases above Rs. 40,000 per month. The high-income earners have shifted their preferences towards other edible oil consumption. The findings of this study suggest that the growth of the per capita incomes and the rapid urbanization in the country further reduces the consumer demand for coconut oil, unless there are effective marketing strategies implemented to promote the CNO consumption in the long run. Both the proportion and rate of CNO use can be increased through an effective campaign via media. Improving the quality and dispelling the misconception among the householders would give better prospects to the coconut oil industry in Sri Lanka.